Cognitive dissonance revisited: A typology of B2B buyers' post-decision 'cognitive states' and its implications for sales professionals. Issue 8 (17th January 2020) - Brooksbank, Roger; Fullerton, Sam
Abstract : Purpose: In revisiting Festinger's theory of cognitive dissonance, this paper seeks to go beyond traditional business-to-consumer (B2C) research parameters and explore the full extent of its potential application within a New Zealand business-to-business (B2B) purchasing context. Design/methodology/approach: The study's core findings are based on four separate focus group discussions with B2B salespeople. Responses were recorded and analysed according to the manifest content of the discussions. These focus groups were preceded by, and followed up with, two other enquiries that sought the perspectives of B2B buyers. Findings: Intended for use as a learning tool for aspiring B2B salespeople and their instructors, a new typology of four generic potential post-decision 'cognitive states' is proposed, which, depending on the scenario at hand, will likely reflect the buyer's mindset. Research limitations/implications: The generalisation of findings may be somewhat limited because the focus groups were drawn from a convenience sample totalling just 20 practitioners. Some participants might also have felt slightly constrained, leading to opinions that are subject to bias. Practical implications: Examples of differing buying scenarios are profiled and explained from the perspective of their implications for salespeople. Suggestions as to how sellers can best accommodate the post-decision cognitive states experienced by their buyers are delineated. Originality/value: Conventional wisdom suggests that post-purchase cognitive dissonance is the sole 'cognitive state' towards which a B2B salesperson needs to be attuned to for the purpose of taking some form of accommodating action. However, this study indicates that three other states relating to the aftermath of a buyer's decision, whether a purchase is made or not, also merit attention.